Digital Transformation of the Learning Process - Students’ Attitudes about Online Teaching - Rakovic, Lazar; Đorđević Milutinović, Lena; Marić, Slobodan; Sakal, Marton; Kapo, Amra (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The COVID-19 pandemic has accelerated the process of digital transformation of higher education institutions. In a very short period, teachers and students abruptly switched to digital environments, which they had not used until then. As online teaching is very different from traditional teaching, teachers and students are faced with numerous new challenges. Online teaching requires a specific environment that primarily implies the availability of adequate technology as well as the skills that both teachers and students should have. Some higher education institutions have completely switched to online mode, while others have practiced a combined (online and offline) mode. The aim of this paper is, based on a questionnaire developed by Bernard et al. (2007), to examine the level of online skills, readiness for online learning and learning initiatives, attitudes about online learning, as well as the desire for online interaction with teachers and colleagues by the surveyed students.